2018
DOI: 10.1080/09538259.2018.1449619
|View full text |Cite
|
Sign up to set email alerts
|

Orthodox Core–Heterodox Periphery? Contrasting Citation Networks of Economics Departments in Vienna

Abstract: The notion of an 'orthodox core-heterodox periphery' structure and the extent of interdisciplinary links have been widely discussed, and partially investigated bibliometrically, within economic discourse. We extend this research by applying tools from social network analysis to citation data of three economics departments located in Vienna, two mainstream and one non-mainstream, to assess their relative citation patterns. We show that both mainstream economics departments follow the asserted core-periphery pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 54 publications
2
13
0
Order By: Relevance
“…For another, we observe that these theoretical outsiders share close ties to other branches of the social sciences (e.g. Glötzl & Aigner 2015), and thereby do not resemble the disciplinary isolation practiced by the economic mainstream. A possible, tentative conclusion to be drawn from this is that the interdisciplinary insularity of economics as diagnosed by Fourcade et al (2015) or Gingras and Schinckus (2012) with respect to econophysics is not primarily due to the idiosyncracies and peculiarities of the subject matter in economics, but rather represents an outgrowth of the dominant economic approach which seems to discount external inputs a priori.…”
Section: Diversitymentioning
confidence: 83%
See 1 more Smart Citation
“…For another, we observe that these theoretical outsiders share close ties to other branches of the social sciences (e.g. Glötzl & Aigner 2015), and thereby do not resemble the disciplinary isolation practiced by the economic mainstream. A possible, tentative conclusion to be drawn from this is that the interdisciplinary insularity of economics as diagnosed by Fourcade et al (2015) or Gingras and Schinckus (2012) with respect to econophysics is not primarily due to the idiosyncracies and peculiarities of the subject matter in economics, but rather represents an outgrowth of the dominant economic approach which seems to discount external inputs a priori.…”
Section: Diversitymentioning
confidence: 83%
“…Notwithstanding these efforts for providing alternative economic approaches with adequate institutional foundations, alternative or “heterodox” schools of thought nowadays only constitute a small fraction inside the economics discipline. While heterodox economists are confronted with a series of exclusionary practices and routines (Dobusch & Kapeller 2009; King 2013), their works also draw on a broader variety of sources and inputs and, hence, exhibit a distinctive, more interdisciplinary communicative pattern (Glötzl & Aigner 2015). Moreover, Glötzl & Aigner (2015) provide additional evidence for this contestedness of economics by pointing to a “mainstream core – heterodox periphery structure” (see, also, Dobusch & Kapeller 2012a) in the citation networks associated with different economics departments at the University of Vienna and the Vienna University of Economics and Business, that differ with respect to their openness for alternative and heterodox approaches in economics.…”
Section: Diversitymentioning
confidence: 99%
“…This article suggests revisiting categories that are often taken for granted. Answering a call made by other researchers (Glötzl and Aigner, 2018), I attempted not to limit myself to a conceptual definition of the categories of orthodoxy and heterodoxy (i.e., a theoretical positioning that approaches or moves away from mainstream theories), but to define them looking at what those categories imply in practice. Indeed, I have chosen to treat the literature considering not only the theoretical proposals that emanate from it, but also the power relationship and the interactions that animate the field.…”
Section: Discussionmentioning
confidence: 99%
“…As Glötzl and Aigner argue, "while the paradigmatic structure of the discourse in economics has received much attention, much of the literature has relied solely on a verbal and (to a lesser extent) statistical description. So far, only a few attempts have been made to empirically investigate whether economics follows an 'orthodox core-heterodox periphery' pattern" (Glötzl and Aigner, 2018). Instead, I will use descriptions of the literature produced by the research field to illustrate the variation in relationship structure between both parts of the field.…”
mentioning
confidence: 99%
“…With respect to the paradigmatic orientation of economics it has been suggested that the discipline has become increasingly narrow (Lee 2004;Colander et al 2004) and follows a "mainstream core-heterodox periphery" structure (Davis 2008;Dobusch and Kapeller 2012;Colander et al 2010). Glötzl and Aigner (2018) find evidence for such a pattern on the department level. Moreover, Bornmann and Wohlrabe (2017, 28) argue that papers published in the JEL field "History of Economic Thought, Methodology, and Heterodox Approaches" are systematically disadvantaged in research evaluations due the lower mean citation rates in the subfield.…”
Section: Concentration In Economicsmentioning
confidence: 90%